An Upper Extremity Risk Assessment Tool Based on Material Fatigue Failure Theory: The Distal Upper Extremity Tool (DUET). (December 2018) - Gallagher, Sean; Schall, Mark C.; Sesek, Richard F.; Huangfu, Rong
Objective: Musculoskeletal tissues repeatedly loaded in vitro fail in accordance with material fatigue failure theory, and there is evidence to suggest that the same process occurs in vivo. The current paper presents a new upper extremity risk assessment tool, the Distal Upper Extremity Tool (DUET), predicated on material fatigue failure theory. Methods: DUET requires an estimate of force exertion level and the number of repetitions performed to derive estimates of damage and probabilities of experiencing a distal upper extremity outcome. Damage accrued over multiple tasks may be summed to estimate the cumulative damage (CD) accrued over a workday. Validation of this tool was performed using five distal upper extremity (DUE) outcomes (involving medical visits and pain) from an existing epidemiological database involving data from six automotive manufacturing plants. Logistic regression was used to assess the association of the log of the DUET CD measure to DUE outcomes. Results: Results demonstrated that the log of the DUET CD measure was highly associated with all five DUE outcomes in both crude analyses and those adjusted for site, age, gender, and body mass index ( p < .01). A model relating the continuous DUET log CD score to the probability of the DUE outcome Injury + Pain Last Year was developed, which demonstrated a significant dose-response relationship. Conclusions: Results suggest that fatigue failure–based risk assessment techniques are highly associated with DUE outcomes and provide support for the notion that an underlying fatigue failure process may be involved in the development of upper extremity musculoskeletal disorders.